The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.7554/elife.62611
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic basis of the EMC-dependent biogenesis of distinct transmembrane clients

Abstract: Membrane protein biogenesis in the endoplasmic reticulum (ER) is complex and failure-prone. The ER membrane protein complex (EMC), comprising eight conserved subunits, has emerged as a central player in this process. Yet, we have limited understanding of how EMC enables insertion and integrity of diverse clients, from tail-anchored to polytopic transmembrane proteins. Here, yeast and human EMC cryo-EM structures reveal conserved intricate assemblies and human-specific features associated with pathologies. Stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 132 publications
8
119
0
Order By: Relevance
“…understanding of how the evolutionarily conserved EMC acts in concert with the Sec61 complex to perform two important, yet apparently discrete, roles during co-translational TMP biogenesis [92]. Firstly, the EMC acts as a membrane insertase that enables the stable integration of certain types of TMD into the lipid bilayer [92][93][94][95]. Hence, following SRP-dependent delivery to the ER (cf.…”
Section: Membrane Insertion Via the Emcmentioning
confidence: 99%
“…understanding of how the evolutionarily conserved EMC acts in concert with the Sec61 complex to perform two important, yet apparently discrete, roles during co-translational TMP biogenesis [92]. Firstly, the EMC acts as a membrane insertase that enables the stable integration of certain types of TMD into the lipid bilayer [92][93][94][95]. Hence, following SRP-dependent delivery to the ER (cf.…”
Section: Membrane Insertion Via the Emcmentioning
confidence: 99%
“…Although not detected by less sensitive methods, comparisons of profile hidden Markov models for archaeal YidC and eukaryotic proteins identified three YidC paralogs in the ER: TMCO1, EMC3, and GET1. Recent single-particle electron cryomicroscopy (cryo-EM) studies yielded structural models for all three paralogs (Bai et al, 2020; McDowell et al, 2020; McGilvray et al, 2020; Miller-Vedam et al, 2020; O’Donnell et al, 2020; Pleiner et al, 2020), which together with the prokaryotic crystal structures reveal a conserved core consisting of a three-TMH bundle interrupted after the first TMH by a cytosolic helical hairpin. In the prokaryotic forms, a sixth, N-terminal peripheral helix is also present.…”
Section: Resultsmentioning
confidence: 99%
“…An outstanding question is whether such non-canonical membrane protein clients are in fact engaged by the EMC for their biogenesis and if so, how? Several studies have reported the loss of multi-pass membrane proteins with loss of EMC functionality 15,23,24 . Often, these studies correlate EMC-dependence with abundance changes at steady-state, rather than monitoring EMC-dependent biogenesis directly.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies from the Weissman lab identified features within the EMC structure that differentially impact TA protein clients when compared to multi-pass membrane proteins including TMEM97, a 4-TMD protein with a similar cytoplasmic N-terminal topology to TRP 23 . One interpretation is that EMC may be able to handle distinct classes of clients through different features.…”
Section: Preprint Gaspar Et Almentioning
confidence: 99%
See 1 more Smart Citation